Can a shape factor in bulk ceramics mitigate unwanted phase transformations?. (1st January 2021) - Kumar, Lakshaman; Arun, Aditya; Chowdhury, Anirban
Abstract: The present work introduces the concept of 'shape strain' to illustrate its beneficial effect to control/avoid any undesired phase transition via consolidation/densification of ceramics; low (4 mole%)-doped ZrO2 ceramics with various dopants have been used for investigation. With ionic radii size difference (of dopant ion and Zr 4+ ) above 30%, CaO-doped zirconia ceramics showed the effect most prominently. The effect was also dependent on the grain boundary mobility of dopants. Controlling final phase evolutions in ceramics is difficult and this effect may serve as remedy if tried with different size fractions of starting powders. Graphical Abstract: Image, graphical abstract